Cross-cultural case study - Pole, Christopher J. 1959-; Burgess, Robert G. (JAI, 2000)
This volume is one of a series of research annuals on qualitative research designed to take up issues and debates in this area that relate to methodology, the relationship between data collection and data analysis, the relationship between theory and method, and the implications of qualitative research for social policy and evaluation.
Keywords: Cross-cultural studies.; Social sciences -- Methodology.; Educational anthropology.; Social research & statistics.; Social Science -- Research.; elektronické knihy; electronic books